STIMULATION OF THE PRIMARY SCHOOL STUDENTS' LEARNING PROCESS - Kilichenko, Oksana; Nakonechna, Larysa (Mountain School of Ukrainian Carpaty, 2021)
The article considers the peculiarities of stimulating primary school students to study. The concepts of "motive", "motivation", "stimulus", "stimulation" are analyzed and generalized. The stages of formation of learning interest in primary school children and its dependence on the organization of the educational process are determined. The level of formation of cognitive interests of students of a class is investigated. Systematized and developed classification of learning stimuli, which includes stimuli, the source of which is the process of activity, stimuli, the source of which is the content of activities, stimuli, the source of which is the relationship between teacher and student, stimuli as a result of student assessment and stimuli arise from the use of different learning tools. The dependence of the use of learning stimuli on the use of teaching methods and forms of organization of the educational process is shown. In particular, the requirements for the use of such teaching methods are specified: specially organized situations of success, the method of creating a situation of interest in a particular subject, the method of creating a situation of novelty of educational material, the method of relying on life experience of students. The expediency of using the method of stimulating the educational process in primary school of various games and game forms of organization of cognitive activity is indicated. Among them are the following groups of games: short games and game shells. The peculiarities of the organization of the educational process in primary school in order to stimulate children's learning through the combination of children in groups are noted. The role of school textbooks as a means of organizing the educational process and the peculiarities of their use in stimulating the learning of primary school students are determined. The article outlines the pedagogical conditions for successful stimulation of children to study. The main ones are to ensure the content of the program material to the mental development of students, the use of various types, forms and methods of learning, use in lessons of collective activities, creativity of teachers in working with textbooks, creating a favorable moral and psychological microclimate.